THE ORIGIN OF A HELIUM ISOTOPE ANOMALY IN THE NORTH OF THE MOUNT ELBRUS REGION - Yakovlev L.E.; Polyak B.G. (My University, 1998)
This study elucidated the source of mantle helium rising to underground fluids in the zone of the recent magmatic activity in the northern Caucasus and the adjacent part of the Scythian Plate. It is shown by way of numerical hydrodynamic modeling that the helium observed in the fluids of the Mount Elbrus and Stavropol Arch regions rises not only through the central feeder of Elbrus Volcano but is also removed from deep-seated magmatic bodies containing mantle helium, which are more widespread than the surface products of magmatic activity.